Crossfire in professional education : students, the professions, and society - Boley, Bruno A. (Pergamon Press, 1977)
Crossfire in Professional Education: Students, the Professions and Society consists of papers collected at a conference of the above subject held in Evanston, Illinois on October 16-17, 1975. This collection of papers explores the pressures and conflicts to which professional education is subject. The focus is on problems facing professional schools that play significant roles in society. One paper discusses society, technology, and professional expertise and then tries to answer the question of balancing the opposing tensions between technology and human values present in the professions. Th.